THE PLAY PROCESS OF THE HOSPITALIZED CHILD, GUIDED BY THE LUDIC MODEL - Dayane Regina dos Santos; Carmem Maria Sales Bonfim; Verônica de Azevedo Mazza; Marilene Loewen Wall; Nen Nalú Alves das Mercês (Universidade Federal do Paraná, 2014)
Playing is fundamental for the healthy development of the child, and during hospitalization can be configured as a care strategy, as long as it is applied systematically and grounded in theory. This study's objective is to report the play process guided by the Ludic Model. The participants were three male children, receiving inpatient treatment in a bone marrow transplantation service, between September and October 2012. Data collection occurred through instruments adapted from the Ludic Model, and progressed in three stages: getting to know the child, caring and playing, and accompanying the evolution of the ludic behavior. The children were participative, demonstrating autonomy, pleasure, and maintenance of the occupational role. The Ludic Model was considered an important tool for guiding the comprehensive and humanized care in this context.